Hubungan Iklim Organisasi dengan Kinerja Pegawai di Bagian Sekretariat Dinas Pendidikan Provinsi Sumatera Barat - Rindu Aria Friska; Hadiyanto Hadiyanto; Nurhizrah Gistituati; Hanif Al Kadri (Journal of Educational Administration and Leadership, 2021)
AbstractThis study examines as well as aims to extract information about the relationship between organizational climate and employee performance at the Secretariat of the Education Office of West Sumatra Province. The method used in this research is correlation research and quantitative methods. All employees of the Secretariat of the Education Office of West Sumatra Province became the population in this study as many as 79 respondents and the sample was 44 respondents. The research instrument used a Likert scale model questionnaire. Analysis of research data using the Product Moment correlation formula in SPSS (Statistical Package and Science). The results of data acquisition for variable X with a mean of 116.57 and a score of 82.07% in the conducive category, each indicator obtained 26.20 completeness of sarpras, 30.36 trust, 31.02 leadership support and 23.14 employee involvement. While the results of the acquisition of variable Y with a mean of 110.80 and a score of 86.53% in the high category, each indicator = 44.64 quality, 33.09 quantity and 38.84 cooperation. Correlation data using SPSS for both variables shows the number 0.001 with a 95% confidence level, if the number shows <0.05 then the variables X and Y are said to be correlated. So it can be concluded that the hypothesis which reads "there is a relationship between organizational climate and employee performance in the Secretariat Section of the West Sumatra Provincial Education Office" can be accepted.